Training with reduced carbohydrate availability increases bone resorption in male academy soccer players: implications for skeletal development during growth and maturation - Stables, R. G.; Anderson, L.; Sale, C.; Hannon, M. P.; Dunn, R.; Tang, J.; Fraser, W.; Costello, N. B.; Close, G. L.; Morton, J. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
During a vital phase of growth and development, academy soccer players exhibit sub-optimal nutrition habits while completing training loads which are comparable to (and can exceed) their adult counterparts. The effect of inadequate carbohydrate (CHO) intake pre-, during and post-training upon skeletal structures remain unknown. Therefore the aim of this study was to test the hypothesis that training with reduced CHO availability increases bone resorption in adolescent soccer players. In a randomised crossover design, ten male players (age: 18±1y) from an EPL academy completed an acute 90-minute field-based training session (occurring between 10:30-12:00) in conditions of high (TRAIN HIGH (TH); 1.5g.kg-1, 60 g, 1.5g.kg-1 and 1.5g.kg-1 consumed at 08:00, during training, 12:30 and 13:30, respectively) or low CHO availability (TRAIN LOW (TL); 0g.kg-1). Participants also completed a non-exercise trial (REST) under identical dietary conditions to TL. Venous blood samples were obtained at 08:30, 10:30, 12:30 and 14:30 for assessment of bone turnover (bCTX and P1NP) and calcium metabolism (PTH and ACa) markers. External training load did not differ (all P > 0.05) between TH and TL, evidenced in total distance (5.6±0.8; 5.5±0.1 km), average speed (81±9; 85±12 m.min-1) and high-speed running (350±239; 270±89 m). bCTX was greater at 12:30 compared with both 10:30 (P = 0.018) and 14:30 (P < 0.01), indicating that training significantly increased bCTX. bCTX was lower in TH compared with both TL (P<0.01; 95%CI: -0.32 to -0.11 ng.mL-1) and REST (P=0.04; 95%CI: -0.31 to -0.01 ng.mL-1) With reference to P1NP, TL was greater than REST (P=0.02; 95%CI: 2.8 to 30.3 ng.mL-1) and approached significance to be greater than TH (P=0.08; 95%CI: -1.3 to 22.2 ng.mL-1). Area under the curve analysis for both bCTX and P1NP was significantly greater (P<0.01 and P=0.03) in TL versus TH. There was no effect of condition for ACa (P=0.67) and PTH (P=0.14). For the first time we quantify the effects of CHO availability upon bone turnover during academy soccer training. Such data demonstrates that training with reduced CHO availability increases bone resorption compared with training with high CHO availability. To that end soccer players should ensure high CHO availability around training to promote skeletal development and reduce injury risk.